Relationship Of Mother’s Knowledge About PHBS With Children Diarrhea Case In Jagasatru Public Health Center, Cirebon City Year 2019 - Lasmaria Marpaung; Cicilia Widiyaningsih; Zainal Abidin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2022)
The high morbidity due to diarrhea in children under five in Indonesia, including at the Jagasatru Public Health Center, Cirebon City, is above 30% in the last 3 years, and there is a tendency to increase every year. Diarrhea is still included in the top 10 most diseases at the Jagasatru Public Health Center, Cirebon City in the last two years. The coverage of household PHBS is still lacking, namely 51.7%, and from several research results there is a relationship between mother's knowledge and PHBS. Thus, we want to know how the relationship between mother/caregiver knowledge about PHBS and the incidence of diarrhea in toddlers at the Jagasatru Public Health Center, Cirebon City. This study is a quantitative study using a case-control design. The sample was 153 people, consisting of 51 cases and 102 controls. The case sample was a child under five who had diarrhea diagnosed by a health center doctor in the last 3 months which was obtained from the medical records of the Jagasatru Health Center and the control sample was a child under five who had not had diarrhea in the last 3 months whose residence was close to the house of the diarrhea sufferer. The number of sample cases: control is 1:2. The data analysis used was univariate, bivariate using chi square and multivariate using multiple logistic regression. The description of the incidence of diarrhea in this study, mothers with less knowledge 38.6, adult mothers 83%, mothers not working 92%, low income 62.7%, PHBS actions were not good 49.7%, mothers gave exclusive breastfeeding 60.8% , mothers wash their hands with soap 50.3%, family latrines meet the requirements 73.2%, treatment of drinking water is boiled until it boils 89.5%, littering 6.6% carry out measles immunization 85%. Variables related to the incidence of diarrhea include knowledge of PHBS mother/caregiver (p value < 0.001, OR 6.16, 95%, CI 2.94-12.86) PHBS measures (p value < 0.001, OR 5.09, 95 %, CI 2.47-10.49) exclusive breastfeeding (p value < 0.001, OR5.09, 95%, CI 2.94-12.86) washing hands with soap (p value < 0.001, OR 11.23 , 95%, CI 4.75-26.59) drinking water treatment (p value 0.004, OR 5.31, 95%, CI 1.558-9.811) landfill (p value 0.016, OR 5.31.95%, CI 0.132-21.54) and measles immunization (p value 0.005, OR 3,910.95%, CI 1.558-9.811. The dominant variable is drinking water treatment (p value 0.002, OR 14.66.95%, CI 2.94). -12.86). In preventing diarrhea, mothers need to increase knowledge about PHBS, promote the importance of PHBS in every Puskesmas activity, inspection of basic sanitation facilities, especially bottled water facilities circulating in the community. Regular development of drinking water refill depots to maintain the quality of water sold to the public.Keywords : Mother's knowledge, incidence of diarrhea